2013
DOI: 10.5194/angeo-31-1833-2013
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for cosmic ray modulation in temperature records from the South Atlantic Magnetic Anomaly region

Abstract: Abstract. Possible direct or indirect climatic effects related to solar variability and El Niño-Southern Oscillation (ENSO) were investigated in the southern Brazil region by means of the annual mean temperatures from four weather stations 2 degrees of latitude apart over the South Atlantic Magnetic Anomaly (SAMA) region. Four maximum temperature peaks are evident at all stations in 1940, 1958, 1977 and 2002. A spectral analysis indicates the occurrence of periodicities between 2 and 7 yr, most likely associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
1
13
0
6
Order By: Relevance
“…For two stations further away, the 22-year cycle was also persistent during the investigated period, but the statistical results indicated a nonlinear relationship between the bidecadal periodicity and temperature variations. In summary, the results of Frigo et al (2013) indicated that a climatic modulation of ∼ 22 years, characteristic of GCRs, was persistent during the last century and was possibly at a maximum in the region closest to the center of the SAMA.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…For two stations further away, the 22-year cycle was also persistent during the investigated period, but the statistical results indicated a nonlinear relationship between the bidecadal periodicity and temperature variations. In summary, the results of Frigo et al (2013) indicated that a climatic modulation of ∼ 22 years, characteristic of GCRs, was persistent during the last century and was possibly at a maximum in the region closest to the center of the SAMA.…”
Section: Introductionmentioning
confidence: 83%
“…However, there are few works reporting the possible indirect influence of the geomagnetic field on climatic variations during the last century (e.g., Vieira and da Silva, 2006;Courtillot et al, 2007;Frigo et al, 2013;Campuzano et al, 2016). Frigo et al (2013) investigated the spectral coherence between the 11-and 22-year solar activity cycles and the yearly average temperatures recorded during the last century at four weather stations located in southern Brazil's coastal region. This region showed smaller values of geomagnetic intensity in the 20th century, due to the presence of the South Atlantic Magnetic Anomaly (SAMA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frigo et al. () argued for a possible influence of GCRs on climate on a regional scale and Artamonova and Veretenenko () concluded that GCRs may influence the process of cyclone and anticyclone formation.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no consensus on a correlation, some studies have continued to assume a relationship between GCR intensity and cloud cover. Frigo et al (2013) argued for a possible influence of GCRs on climate on a regional scale and Artamonova and Veretenenko (2011) concluded that GCRs may influence the process of cyclone and anticyclone formation. Shaviv (2002Shaviv ( , 2003 proposed that the occurrence of ice-age epochs on the Earth was influenced by the solar system crossing through the spiral-arms of the Milky Way.…”
Section: Introductionmentioning
confidence: 99%